Executive Compensation, Green Innovation and Corporate Social Responsibility: Evidence from Chinese Listed Company - Yao, Miao (2022)
This paper selects Chinese A-share listed companies from 2010 to 2020 and explores corporate green innovation from the perspectives of both executive compensation and corporate social responsibility. The research results show that executive salary incentives have a significant positive relationship with green innovation, while equity incentives exert a negative impact on it. This negative effect is significant in firms with a longer establishment, firms with mature management, and firms with two separate positions of chairman and the CEO/general manager. In addition, further tests reveal that the degree of corporate CSR fulfillment has a positive moderating effect on the positive relationship, while it has no effect on the negative connection. The results of the robustness test indicate that the obtained findings are reliable. This research is of great significance for promoting enterprises to improve equity incentive reform, enhance the development of green innovation, and strengthen the performance of corporate social responsibility.